И.ЮСУПОВ ЛИРИКАСЫНДА МАҚТЫМҚУЛЫ ДӘСТҮРЛЕРИ - Ҳайтбаева, В. (SCIENCE and SOCIETY, 2025)
The article studies the poetic traditions of Makhtumkuli in the didactic-philosophical direction in the poetry of I.Yusupov. It is proved that the poems included in the series "On the Path of Makhtumkuli" by I.Yusupov are in harmony with Makhtumkuli's poems in terms of formal, ideological-thematic and genre-stylistic features, and that his poetry continues Makhtumkuli's literary traditions and philosophical thoughts.
Keywords: literary tradition; Mahtumkuli's work; I. Yusupov's poetry; the murabba genre; poetic tradition; philosophical lyrics